2013
DOI: 10.1590/0102-311x00115112
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and physical inactivity during pregnancy: a cross-sectional study nested in the BRISA cohort study

Abstract: The aim of this study was to investigate the association between mental health and physical inactivity in 1,447 pregnant women in the second trimester of pregnancy. Subjects answered the short version of the International Physical Activity Questionnaire. Symptoms of depression and anxiety, and stress levels were assessed using the Center for Epidemiological Studies Depression Scale, the Beck Anxiety Inventory and the Perceived Stress Scale, respectively. The rate of physical inactivity was low (39.8%). The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 61 publications
1
13
0
3
Order By: Relevance
“…Studies have reported the prevalence of stress and anxiety during pregnancy as 6% to 78%; that is, 6% of the population is reportedly exposed to high levels of stress and 78% is exposed to low or moderate levels (7)(8)(9). Stress during pregnancy can be associated with adverse pregnancy outcomes such as miscarriage, fetal weight loss, increased stress hormone levels, chronic hypertension, premature birth, infant mortality, changes in endocrine secretion, changes in hypothalamic-pituitary function, suppressed immune system, changes in the number of lymphocytes and reduced CD4/CD8 ratio, nausea, vomiting, preeclampsia, and some degree of mental disorder (10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported the prevalence of stress and anxiety during pregnancy as 6% to 78%; that is, 6% of the population is reportedly exposed to high levels of stress and 78% is exposed to low or moderate levels (7)(8)(9). Stress during pregnancy can be associated with adverse pregnancy outcomes such as miscarriage, fetal weight loss, increased stress hormone levels, chronic hypertension, premature birth, infant mortality, changes in endocrine secretion, changes in hypothalamic-pituitary function, suppressed immune system, changes in the number of lymphocytes and reduced CD4/CD8 ratio, nausea, vomiting, preeclampsia, and some degree of mental disorder (10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Our study did not ask pregnant women about specific physical activities. However, few women in our sample reached very high activity levels, and most physical activity in our sample probably involved household chores 30 . Thus, based on our data it seems that physical activity during pregnancy is not harmful to the fetus.…”
Section: Discussionmentioning
confidence: 61%
“…Centrándonos en la frecuencia de síntomas percibidos en la etapa final de embarazo, observamos como en todos los síntomas relacionados con el aspecto psicológico los porcentajes de embarazadas que perciben dichos síntomas son algo superiores en el grupo de embarazadas inactivas que en el grupo de embarazadas activas, aunque hay que recalcar la ausencia de diferencias significativas. Resultados similares encontramos en la literatura científica, donde se muestra una correlación positiva entre el cumplimiento de las recomendaciones de actividad física (Demissie et al, 2011;Loprinzi et al, 2012) o la participación en programas de ejercicio físico (Perales et al, 2015;Robledo-Colonia et al, 2012) y la prevalencia de síntomas depresivos, o entre el cumplimiento de las recomendaciones de actividad física y la percepción de ansiedad (Da Costa et al, 2003;Takahasi et al, 2013). En cuanto a la limitación provocada en la vida diaria por los síntomas psicológicos en la etapa final del embarazo, encontramos diferencias significativas en los síntomas de sentimientos depresivos y ansiedad.…”
Section: Discussionunclassified
“…De la misma manera la actividad física tiene un efecto positivo en modificación de la frecuencia y severidad de los síntomas relacionados con el embarazo (Foxcroft et al, 2011), como es el caso de los síntomas relacionados con el aspecto psicológico como la depresión (Loprinzi et al, 2012;Perales et al, 2015;Robledo-Colonia et al, 2012) o la ansiedad (Da Costa et al, 2003;Takahasi et al, 2013).…”
Section: Introductionunclassified